2006
DOI: 10.1179/174329006x120609
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature combustion synthesis for preparation of TiC reinforced Fe based composites under electric field

Abstract: In the present paper, the combustion synthesis processes of the system of Fe based composites, mainly containing Fe-Ti-C, under an electric field was studied by using a Gleeble 1500D thermal simulation instrument. The results showed that there was a great change in temperature inside the sample under rather low temperature, compared with that in the self-propagating high temperature synthesis (SHS) processes. This indicated that a reaction may occur, which led to a great deal of heat release. Analyses by X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In this process, the whole sample combusts without wave propagation as in a thermal explosion mode. 9,10 To the authors’ knowledge, no report has been found on electric field activated CS of the Fe–Ti–C system except their research group. It was found that the Fe–Ti–C system with the iron content up to 75 wt-% can be synthesised under the action of an electric field, and the ignition temperature is only 735°C.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the whole sample combusts without wave propagation as in a thermal explosion mode. 9,10 To the authors’ knowledge, no report has been found on electric field activated CS of the Fe–Ti–C system except their research group. It was found that the Fe–Ti–C system with the iron content up to 75 wt-% can be synthesised under the action of an electric field, and the ignition temperature is only 735°C.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Groza[10] have investigated that a lot of Joule heat could be generated by a localized area of high resistance and provided that the current should be compelled to choose the least resistance path through the powders. Under the proper simplified condition, the formula of the Joule heat generated by the current passing through the compact according to Joule-Lenz's law could be shown as[11] : Rt I Q…”
mentioning
confidence: 99%
“…Different from their method, the outside ignited equipment isn't needed in our research, and an electric field play the roles not only in maintaining and controlling the process of combustion, but also in promoting diffusion process among the reactant atoms at low temperature in order to reduce the starting temperature of reaction. 7,8) TiC-Fe composites which can be used as cutting, machining and wear resistance materials draw much attention because of their extremely high hardness and toughness attributes. Although there are a few reports about the combustion synthesis of TiC-Fe composites from Ti, C and Fe powders, all of them are based on conventional combustion synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…7,8) In order to overcome the shortcoming of conventional CS, electric field activated CS is a effective method of preparing high quality composites. At present, there is none of report about electric field activated the system of Fe-Ti-C combustion synthesis except for our research group.…”
Section: Introductionmentioning
confidence: 99%